ASSESSING THE ROLE OF DIGITAL BANKING IN PROMOTING FINANCIAL INCLUSION IN EMERGING MARKETS - Nida Garnida Fitrianti; Anggun Yolistina; Raden Roro Fatmasari (PT. Kreatif Indonesia Satu, 2024)
Background:Financial inclusion remains critical with 1.4 billion adults globally unbanked. Digital banking offers accessible, affordable services to underserved populations. Aims:This study assesses digital banking's role in promoting financial inclusion across diverse emerging market contexts. Research Method:Using mixed-methods, we analyzed adoption patterns across five emerging markets, including quantitative metrics and qualitative interviews with 120 users and 45 providers. Results and Conclusion:Digital banking increased financial access by 23%. Mobile banking achieved 68% adoption among previously unbanked, with costs reduced 40%. Barriers include digital literacy gaps (35%), infrastructure limitations, and trust concerns. Contribution:The study provides empirical evidence of digital banking effectiveness in financial inclusion while identifying critical success factors and persistent challenges requiring policy intervention.